2011
DOI: 10.1002/cjce.20487
|View full text |Cite
|
Sign up to set email alerts
|

SAG mill system diagnosis using multivariate process variable analysis

Abstract: Semi-autogenous grinding (SAG) of ore plays a critical role in a mineral processing plant. In SAG operations, abnormal conditions, such as overload or insufficient ore holdup, often result in inefficient production and unstable operation. It is, therefore, essential to monitor the process using effective technology so that abnormal or faulty conditions can be detected and addressed in a timely manner. In this study, investigation is focused on applying multivariate analysis in the monitoring and diagnosing of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…This view and these statistics can be used to determine whether a fault may have occurred and offer a starting point for root cause analyses. The application to SAG mill monitoring with PCA has also been considered by Ko and Shang (2011). Their study indicated that PCA is a suitable approach to visualize overall mill process performance, as well as to detect abnormal process conditions.…”
Section: C) Mill State Densitymentioning
confidence: 99%
“…This view and these statistics can be used to determine whether a fault may have occurred and offer a starting point for root cause analyses. The application to SAG mill monitoring with PCA has also been considered by Ko and Shang (2011). Their study indicated that PCA is a suitable approach to visualize overall mill process performance, as well as to detect abnormal process conditions.…”
Section: C) Mill State Densitymentioning
confidence: 99%
“…PCA, using the Q and T 2 test statistics, is also trained as a process monitoring method for comparison to SLLEP-LDA. Ko and Shang introduce this technique for SAG monitoring and demonstrate its ability to detect process abnormalities for SAG mill operation. However, this study does not identify which abnormalities are overload events.…”
Section: Case Study: Sag Mill Overloadmentioning
confidence: 99%
“…We apply SLLEP to detect the early onset of a semiautogenous grinding (SAG) mill overload. We show that SLLEP with linear discriminant classification beats the best-in-class technique in the industry, PCA with T 2 and Q test statistics, 13 for monitoring a SAG mill overload. Furthermore, we discuss a simple method to interpret the classification output of the SLLEP feature space to estimate the severity of a process abnormality and provide operators with an information-rich univariate measurement.…”
Section: Introductionmentioning
confidence: 98%